Biomass-Derived Plant Extracts in Macromolecular Chitosan Matrices as a Green Coating for PLA Films - Lidija Fras Zemljič; Tjaša Kraševac Glaser; Olivija Plohl; Ivan Anžel; Vida Šimat; Martina Čagalj; Eva Mežnar; Valentina Malin; Meta Sterniša; Sonja Smole Možina (Journal of Functional Biomaterials, 2022)
Due to the growing problem of food and packaging waste, environmental awareness, and customer requirements for food safety, there is a great need for the development of innovative and functional packaging. Among these developments, the concept of active packaging is at the forefront. The shortcoming in this area is that there is still a lack of multifunctional concepts, as well as green approaches. Therefore, this work focuses on the development of active chemical substances of natural origin applied as a coating on polylactic acid (PLA) films. Biopolymer chitosan and plant extracts rich in phenolic compounds (blackberry leaves—Rubus fruticosus, needles of prickly juniper—Juniperus oxycedrus) obtained from plant biomass from Southeastern Europe were selected in this work. In order to increase the effectiveness of individual substances and to introduce multifunctionality, they were combined in the form of different colloidal structural formulations. The plant extracts were embedded in chitosan biopolymer particles and dispersed in a macromolecular chitosan solution. In addition, a two-layer coating, the first of a macromolecular chitosan solution, and the second of a dispersion of the embedded extracts in chitosan particles, was applied to the PLA films as a novel approach. The success of the coatings was monitored by X-ray photoelectron spectroscopy (XPS) and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), and the wettability was evaluated by contact angle measurements. Scanning electron microscopy SEM tracked the morphology and homogeneity of the coating. Antioxidation was studied by DPPH and ABTS spectrophotometric tests, and microbiological analysis of the films was performed according to the ISO 22196 Standard. Desorption of the coating from the PLA was monitored by reducing the elemental composition of the films themselves. The successful functionalization of PLA was demonstrated, while the XPS and ATR-FTIR analyses clearly showed the peaks of elemental composition of the extracts and chitosan on the PLA surface. Moreover, in all cases, the contact angle of the bilayer coatings decreased by more than 35–60% and contributed to the anti-fogging properties. The desorption experiments, due to decrease in the concentration of the specific typical element (nitrogen), indicated some migration of substances from the PLA’s surface. The newly developed films also exhibited antioxidant properties, with antioxidant ABTS efficiencies ranging from 83.5 to 100% and a quite high inhibition of Gram-positive Staphylococcus aureus bacteria, averaging over 95%. The current functionalization of PLA simultaneously confers antifogging, antioxidant, and antimicrobial properties and drives the development of a biodegradable and environmentally friendly composite material using green chemistry principles.